INSECTICIDAL ACTIVITY OF THE BACILLUS THURINGIENSIS-BASED BIOPREPARATION BIOTURIN AGAINST THE PEST OULEMA MELANOPUS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article presents the results of evaluating the biological efficacy of the Bacillus thuringiensis-based biopreparation Bioturin as a safe alternative to broad-spectrum chemical insecticides in controlling the economically significant pest Oulema melanopus (cereal leaf beetle) in wheat crops under the conditions of Tashkent, Syrdarya, and Surkhandarya regions. The preparation was applied at a rate of 2.0–3.0 liters per hectare. At the application rate of 3.0 liters per hectare, Bioturin reduced the Oulema melanopus population by an average of 75.9% on the 14th day after treatment. The results confirmed the potential of Bioturin as an effective biological alternative to chemical insecticides. Other significant research findings are also discussed.